Discursos sobre letramento na mídia digital: uma análise do blog Exequi - Santana, Mariana Galdino (2019)
Nowadays, we can notice the national media such as radio, newspaper and digital newspaper increasing their attention to issues related to education, especially languages. This paper is about the literacy discourse that circulates in a blog named Exequi, whose national posts are published by CBN radio weekly, those posts are a permanent session of the program and they are also released on streaming plataform. Observing the variety of notions about literacy the following questions guide this research: 1) Which literacy discourses circulate in the main agents and digital media in the Exequi blog? 2) Which discourses about education are supported in this journalistic sphere of communication? How this discourses can contribute to the confrontation related to the literacy of social groups that are not acquainted with reading and writing practices considered relevant for formal education? Which propositional actions can be taken to insert new positions into the discussion in the educational media sphere? To answer these questions we set as general aim of this research to study the different concepts of literacy elaborated by scholars who have been researching the complex subject of literacy (s). Considerating the concepts of literacy related to the dialogical studies of discourse, we propose as specific aims: a) through a dialogical-discourse analysis, to study which discourses of literacy, also know as social voices, circulate in the Exequi blog; b) to identify the blog position about modernity and postmodernity; c) to propose alternatives about blogs creation that brings social voices about literacy. What motivated us to develop this study was the concerning about the literacy discourses in the digital media. The theoretical basis for this research is the dialogical language conception of Bakhtin and his Circle. We seeked support in Street (2014) and Buzzato (2009), to work the literacy concepts. The methodological procedures are based on two fronts: one is investigative and the other is propositive. For the first, were executed procedures of records generation - surveys on websites, blogs, platforms, etc. – all of them were accomplished by the researcher in the light of the virtual ethnography, in which the Exequi blog was delimited as data analysis under the dialogical-discursive perspective for the language study of Bakhtin's inspiration. For the second, a blog was created taking into account issues related to centrifugal forces and plurilingualism. The results point to the presence of a pragmatic action in the construction of meaning, so that the approach of the idea of excellence and justice constituted a rhetorical strategy of discourse, what is, a discursive imposture.